Determination Of The Company Capital Structure On The LQ45 Index - Lilik Pirmaningsih; Tantri Bararoh (Cita Konsultindo Research Center, 2022)
The purpose of this study is to test and analyze the effect of profitability, asset tangibility, company growth, company size, opearating leverage, and company age on the capital structure. The research sample used in this study is companies that are included in the LQ45 index list on the Indonesia Stock Exchange in 2019-2021. The analysis technique used in this study is multiple linear regression. The results of the study show that asset tangibility, company size, operating leverage, and company life significantly affect the capital structure.